answersLogoWhite

0


Best Answer

4 solve t

User Avatar

Alexis

Lvl 3
โˆ™ 2021-10-19 22:53:48
This answer is:
๐Ÿ™
1
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards
More answers
User Avatar

Andrew Small

Lvl 5
โˆ™ 2021-10-20 00:19:05

it is four t

User Avatar

Add your answer:

Earn +20 pts
Q: What 1 + 3t =4 solve t?
Write your answer...
Submit
Related questions

Solve 4t-1 equals t plus 2?

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1


T-3t plus 2t plus 4?

if you mean T-3t+2t+4 (T and t is different variables):T-3t+2t+4=T-t+4if you mean t-3t+2t+4:t-3t+2t+4=4


Solve for t in the equation 3t plus 7 equals 2t-5?

3t + 7 = 2t - 5 3t = 2t - 12 t = -12


how do i solve 3 x t x t =?

it became 3t^2


Find the value in the equation of T plus 5 plus 3T equal 1?

T + 5 + 3T = 1 Simplify the terms, T and 3T (think 1 apple plus 3 apples) 4T + 5 = 1 Subtract 5 from both sides. 4T = -4 then divide both sides by 4 to get T by itself. T = -4/4 T = -1 To check, substitute T = -1 wherever you see T in your original equation. T + 5 + 3T = 1 (-1) + 5 + 3(-1) = 1 4 - 3 = 1 1 = 1 (check)


How do you solve 3t-6 equals t-2?

I'm guessing you want to solve for t so: 3t-6=t-2 u bring the t from the left side and subtract it from the 3t and u get 2t b/c 3-1 is 2 2t-6=2 then u bring the 6 over to the right side and u add it to the 2 and u get 2t=8 and then u divide 8 by 2 and u get t=4 if u dont understand u shud probably go to an algebra teacher because they can explain it better


What is the answer to 22 equals 4 plus 3t?

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6


What is the answer for st plus 3t equals 6 solve for s?

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3


What does t represent in this equation 3t plus 4 equals t plus 13?

Gather like terms: 3t - t = 13 - 4 ie 2t = 9 so t =4½ Check: 3t = 13½ + 4 = 17½, 4½ +13 = 17½ QED


X equals 3t-12 solve the equation?

15


T T plus T over 3T someone gave me this brain teaser this is ment to make a word or phrase?

From a mathematical point of view, this comes out as (TxT+T) / 3T T2 + T / 3T 1/3T + 1/3 Well....no luck. I believe there is a more riddle-type answer like this: LOheadVE heels (head over heels in love).


What is 17 equals 3t-4?

It is an equation. Taking it step by step: 17 = 3t - 4 17 + 4 = 3t 21 = 3t 7 = t So the value of t is 7.


Can you find the value of T in the equation T plus 5 plus 3 T equals 1?

t+5+3t = 1(subtract 5 from each side)t+3t = -4(combine like terms)4t = -4(divide both sides by 4)t = -4/4t = -1


Which equation is an xy-equation for the parametric equations x equals -3t plus 4 and y equals t plus 1 where 1 t 4?

You're looking to combine these two equations into one that uses only the terms x and y, right? In that case, we can take either of those equations, solve it for t, and plug it's results in place of t in the other equation: x = -3t + 4 y = t + 1 y - 1 = t x = -3(y - 1) + 4 x = -3y + 3 + 4 x = 7 - 3y You can of course solve this for y as well: -3y = x - 7 y = (7 - x) / 3


How do you simplify 7 plus t-3t?

4


T plus 8 equals 2-3t?

t+8 = 2-3t add 3t to both sides: 4t+8 = 2 take 8 away from both sides: 4t = -6 divide both sides by 4: t = -6/4 = -3/2


How do you solve 5t plus 2 equals 3t-2t plus 5?

5t + 2 = 3t - 2t + 5 Collect like terms 5t - 3t + 2t = 5 - 2 4t = 3 t = ¾ Check: 5 x 3/4 = 3¾ + 2 = 5¾; 3x¾- 2x¾ + 5 = 5¾ QED


What is t plus t plus 3t plus 1 in math?

5t + 1


How do you factor 3t2 - 3t - 6?

3(t - 2)(t + 1)


What does 3t multiplied by t equal?

3 t squared (3t^2)


Which product equals to 3t-12?

15


How do you solve one fifith times three t minus six equals t plus six tenths?

By writing it out so you get: (1/5)*3t-6=t+(6/10) multiply and divide: (1/5)*3t=3t/5 6/10=3/5 which gives you: 3t/5-6=t+(3/5) put the variables on one side and the non-variable numbers on the other by adding and subtracting: 3t/5-6=t+(3/5) -3t/5 -3t/5 -6=2t/5+3/5 -3/5 -3/5 -33/6=2t/5 now multiply by the denominator on the variable side and divide by the numerator on the variable side (except the variable itself): -33/6=2t/5 *5 *5 -165/6=2t /2 /2 -165/12=t Now, reduce: -165/12=-55/4=-13.75 So, t=-55/4 or t=-13.75


What does t equal in the eqation 5-3t equals 0.77?

5-3t = 0.77 -3t = 0.77-5 -3t = -4.23 t = 1.41


How do you factor 6t2-7t-5 divided by 3t-5?

6t2 - 7t - 5 = (3t - 5)*(2t + 1) So (6t2 - 7t - 5)/(3t - 5) = 2t + 1 provided that t is not 5/3


Can you factor the expression three t squared plus sixteen t plus five?

(3t + 1)(t + 5)